Дослідження в м. Харків і Харківській обл. в 2009 р. (за матеріалами експертиз) - Шрамко, І.Б.; Голубєва, І.В.; Задніков, С.А.; Пеляшенко, К.Ю. (Археологічні дослідження в Україні, 2010)
Results of archaeological examinations at the territory of Kharkiv and Kharkiv Oblast in 2009 are presented. The information obtained concerns various periods: from the Bronze Age to the Late Mediaeval period.